Roland Barthes's Travels in China: writing a diary of dissidence within dissidence?. Issue 2 (23rd February 2016) - Stafford, Andy
Abstract : Considering the style of writing employed in his diaries Travels in China, published posthumously and without the author's permission, this article traces Roland Barthes's uneasy resistance to Maoist propaganda during and after his trip to China with Tel Quel in April 1974. By analysing the elliptical and easily distracted manner in which he records his impressions, the conclusion is that the diaries prefigure the quandary in which Barthes finds himself when asked for his views on China by the French daily newspaper Le Monde on his return. His 'suspension of judgement' in the subsequent front-page article is qualified by the seminar on China that he gives to his students, and which has been recently published in Le Lexique de l'auteur, the experiment on the 'self' and the social image of the writer which becomes Roland Barthes by Roland Barthes .